Loss investigations involving heating element failures: Fire, water, and personal injury. (May 2017) - Green, Lee; Shuttlesworth, Michael; Buc, Elizabeth C
Sheathed heating elements, or calrod heaters, are used in a variety of appliances and processes to heat a media (water, air, other fluids). Examples of appliances that utilize sheathed heating elements are water heaters (trough and residential), dishwashers, dry saunas, and RV refrigerator cooling units. The construction and use of various heating elements are reviewed with a focus on design features which may contribute to failures and safety features which should prevent catastrophic failures. This article will expand on NFPA 921 (2014) Section 26.5.7 describing various heating element failures as the root cause of not only fires but also personal injury (e.g. burns, electrocution) and water losses. Common causes and failure modes of heating elements, from case studies and literature, are presented. A basic protocol for the thermal and material characterization and laboratory examination and testing of heating elements and failures is provided.